Size matters : effect of screen setup on muscle activity and posture in computer work - Dahlqvist, Camilla; Arvidsson, Inger; Löfqvist, Lotta; Nyström, Marcus ; 0000-0002-2089-9012; Glimne, Susanne; Hemphälä, Hillevi ; 0000-0003-1206-2172 (Ergonomics, 2025)
This research aims to investigate and compare how computers work on five different workstation setups of multiple or large screens and viewing distances (27-inch and 49-inch at 70 or 90 cm viewing distance) affect muscular load in neck/shoulders, working postures, and perceived exertions of non-presbyopic participants. The electrical activity in the trapezius shoulder and trapezius neck muscles, and work postures of the head and back were recorded with objective, technical methods. The perceived exertions in the neck/shoulder and eyes, and the participants' opinions of the different workstations, were collected. Overall, the 49-inch curved screen with a viewing distance of 90 cm was quantitatively recorded and qualitatively rated as the best setup of all five workstations included in the study. The 49-inch screen was also objectively and subjectively rated to be better than 2 × 27-inch screens. The 2 × 27-inch V-formation setup was subjectively favoured compared to the 2 × 27-inch L-formation setup.